2003
DOI: 10.1159/000069121
|View full text |Cite
|
Sign up to set email alerts
|

Air Travel-Associated Venous Thromboembolism

Abstract: Long-distance air travel is increasing and cases of venous thromboembolism (VTE) following air travel have attracted both considerable public attention and legal claims against airlines. VTE is a common disorder worldwide with a notably high incidence in older individuals. Many biochemical factors that lead to, or accentuate, thrombus formation are associated with increased risk of VTE. These factors include thrombophilia, activated protein C resistance and factor V Leiden, prothrombin gene mutation, antiphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…2 6 Venous thrombosis and consequent pulmonary embolism after long-distance travel has been widely recognised and reported in the literature. [6][7][8][9] Recently, some reports described a possible association between long travelling and stroke through paradoxical embolism and designated this condition ''economy class stroke syndrome'' (ECSS). [10][11][12][13][14][15][16][17] On the basis of these reports, we questioned whether this clinical stroke condition can be relevant in the care of patients in a European stroke care centre.…”
mentioning
confidence: 99%
“…2 6 Venous thrombosis and consequent pulmonary embolism after long-distance travel has been widely recognised and reported in the literature. [6][7][8][9] Recently, some reports described a possible association between long travelling and stroke through paradoxical embolism and designated this condition ''economy class stroke syndrome'' (ECSS). [10][11][12][13][14][15][16][17] On the basis of these reports, we questioned whether this clinical stroke condition can be relevant in the care of patients in a European stroke care centre.…”
mentioning
confidence: 99%
“…Recently we observed two tourist-patients with Factor V Leiden, one of them developed PE after surgery [50]. The physical factors related to these events are prolonged venous stasis associated with long periods of immobility, exposure to cabins with low humidity, and low concentrations of oxygen [51]. During the process of establishing a medical program for this patients it is important to instruct them to stick to the prophylactic guides to prevent DVT and PE that airlines recommend like performing exercises with their feet and legs, walk frequently through the cabin alleys, as well as using adequate elastic compression stockings, avoid alcohol and dehydration during the flight.…”
Section: Recent Prolonged Tripsmentioning
confidence: 99%
“…Iqbal et al. () reported that individual factors (e.g., age, weight, oral contraceptives, medical history) and in‐flight factors contribute to air travel–related VTE. Flight factors related to VTE include immobility and the cabin environment, which is characterized by low relative humidity (RH), hypobaria, and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Increased incidence of venous thromboembolic events (VTE) following long-haul flights is now well documented (Boccalon et al, 2005), and the link between VTE and air travel has been discussed (Gavish and Brenner, 2011;Morio et al, 2005;Nicholson et al, 2003). Iqbal et al (2003) reported that individual factors (e.g., age, weight, oral contraceptives, medical history) and in-flight factors contribute to air travel-related VTE. Flight factors related to VTE include immobility and the cabin environment, which is characterized by low relative humidity (RH), hypobaria, and hypoxia.…”
Section: Introductionmentioning
confidence: 99%